Langmuir dark solitons in dense ultrarelativistic electron-positron gravito-plasma in pulsar magnetosphere - U. A., Mofiz; Amin, M. R. (© 2013 Springer, 2016)
This article was published in the Astrophysics and Space Science [© 2013 Springer Science+Business Media Dordrecht] and the definite version is available at : http://dx.doi.org/10.1007/s10509-013-1385-6 The Journal's website is at: http://link.springer.com/article/10.1007%2Fs10509-013-1385-6